Diagnostic and therapeutic value of implantable loop recorder: A tertiary care center experience. Issue 1 (4th December 2018) - Padmanabhan, Deepak; Kancharla, Krishna; El‐Harasis, Majd A.; Isath, Ameesh; Makkar, Nayani; Noseworthy, Peter A.; Friedman, Paul A.; Cha, Yong‐Mei; Kapa, Suraj
Abstract: Background: Implantable loop recorders (ILRs) are effective in achieving symptom‐rhythm correlation. However, diagnostic yield in routine clinical practice is not well established. Methods: Patients undergoing ILR implantation between April 2010 and May 2015 were included. All devices were enrolled in remote monitoring with automatic arrhythmia detection and P sense algorithms switched "ON." Symptom‐rhythm correlation was assessed and changes in management were recorded. Results: A total of 312 patients (57% male, age 53 ±  22 years; median CHADS2VaSc score  =  1) were included in this study. ILRs were implanted for evaluation of syncope in 206 (66.0%), presyncope in 23 (7.4%), unexplained palpitations in 51 (16.3%), and cryptogenic stroke in 27 (8.7%) patients. ILR monitoring yielded a diagnosis that changed management strategy in 146 (46.8%) patients over a median of 12 (1‐42) months. Out of 163 (52.2%) patients with symptoms during the monitoring period, 100 (61.3%) had an arrhythmia. ILR was useful in ruling out an arrhythmic cause for symptoms in 63 (38.7%) patients. ILR results led to pacemaker implantation in 23 patients (7.4% overall and 11.2% of those with syncope) after median follow‐up of 3 months. A new diagnosis of atrial fibrillation was made in 38 (12.2%) patients, 11 of whom were initiated on oral anticoagulants. ILR results led to pacemaker implantation in 31 patients (9.9% overall and 19.0% of those with syncope) after median follow‐up of 3 months. A new diagnosis of atrial fibrillation was made in 38 (12.2%) patients, nine of whom were initiated on oral anticoagulants. Overall, ILR led to a change in management in 47% patients with a number needed to implant of 2.1 to change management. Conclusion: ILR monitoring is effective in achieving symptom‐rhythm correlation and results in changes in management in nearly half of implanted patients. Additional studies are needed to evaluate cost efficacy of ILR and the optimal monitoring duration.